Futuristic Urban Style With Reversible Clothing - Arsy, Fadillah Dzil; Rahmat, Fadri; Yanuarmi, Dini; Trisnawati, Desi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The work entitled “Futuristic Urban Style with Reversible Technique” is a process of designing and realizing clothing that integrates contemporary urban concepts with futuristic aesthetics through an innovative and functionality-oriented design approach. The creation of this work is motivated by the development of a dynamic, expressive urban lifestyle, and is influenced by streetwear culture and global Trends that are moving towards adaptive and sustainable forms of fashion. The concept design was carried out through stages of visual exploration, literature study, Trend analysis, moodboard preparation, alternative sketch creation, and the design selection process which is realized into three levels of clothing Ready to wear, Ready to wear deluxe, and Haute couture so that the work show has the theme “backblack”. The three levels represent different design developments based on the level of technical complexity, material exploration, and construction complexity. The artist uses materials such as leather, denim, and textiles with futuristic characters, combined with fabric manipulation quilting techniques and manual abstract paintings as the main visual elements. This work aims to construct a futuristic urban fashion identity that not only prioritizes artistic and experimental values, but also responds to the needs of urban society for practical, flexible, and highly durable clothing. This creation is expected to contribute to the development of contemporary fashion design in Indonesia, especially in the development of reversible techniques and exploration of sustainability-based design. In addition, this work functions as a form of artistic practice that reflects the relationship between future aesthetics, textile technology, and the dynamics of urban culture in the realm of modern fashion.